Pengaruh iklim sekolah terhadap kepuasan penerapan inklusi: studi persepsi orangtua dengan anak berkebutuhan khusus di kota Depok - Anisa Rahmadani; Achmad Ushuluddin; Abdullah Hakam Shah (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
As an education system that becomes a new choice, the implementation of inclusive education still faces many challenges. This research was conducted due to the limited research on school climate with parents' perspective about inclusion at the micro level in Kota Depok. The purpose of this study is to examine the effect of parents' perception about school climate toward school sastisfaction in Kota Depok. This quantitative correlational study involve 72 parents who had special needs children who attend inclusive public and private school. Parents completed two self-report questionnaires: Parental Perception of Inclusion Climate Scale and Satisfaction of School Inclusion Survey. The results show there are significant differences regarding satisfaction, with parents from private school tend to more satisfied about inclusive that parents from public school. A regression analysis was performed and confirmed that parents perception about school climate were predictors of parents satisfaction about inclusive school. These finding provide insight that the main consideration for satisfaction according to parents is the support provided by all school staff and teachers. Stakeholders can consider providing understanding to all school stakeholders about the importance of support, both instrumental and emotional.